Between the Job Creation Act and Labor Act: What’s Specific Time Employee Agreement (PKWT)? - Ariawan Gunadi; Suwinto Johan; Amad Sudiro (Nagari Law Review, 2022)
President Jokowi signed the Law of the Republic of Indonesia No. 11 of 2020 on Job Creation (UU Cipta Kerja), but the Constitutional Court (MK) decided to conduct a judicial review. According to the Constitutional Court, the government must revise the Job Creation Law within two years. Two of the five petitioners for judicial review express concern about the Job Creation Law's inclusion of Specific Time Employee Agreements (PKWT). A Specific Time Employee Agreement is a contract between a business/employer and its employees for a specified period. The purpose of this study is to examine Specific Time Employee Agreements. This study employs a normative judicial methodology. The research is unique in discussing Specific Time Employee Agreements from two perspectives: the worker and the employer. Additionally, this research examines how Specific Time Employee Agreements have been implemented in practice thus far. The research concludes that workers lack understanding of Specific Time Employee Agreements, raising concerns about the Job Creation Law. The absence of a formulation regarding precarious work creates legal uncertainty for workers. Ineffective communication between the employer and employees has raised suspicions regarding the Specific Time Employee Agreement between the two parties. The Job Creation Law's socialization of labor cluster legislation requires improvement. To avoid misinterpretation, the definition of non-permanent work must be clarified